2016
DOI: 10.1016/j.foodhyd.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of β-carotene in alginate-based hydrogel beads: Impact on physicochemical stability and bioaccessibility

Abstract: 24Delivery systems are needed to protect carotenoids in foods, but release them at an 25 appropriate location within the gastrointestinal tract (GIT). In this study, β-carotene was 26 incorporated into three different delivery systems: free lipid droplets; filled hydrogel 27 beads formed using 0.5% alginate ("0.5% beads"); and, filled hydrogel beads formed 28 using 1% alginate ("1% beads'). Hydrogel beads were fabricated by injecting an alginate 29 solution into a calcium ion solution using an extrusion device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(54 citation statements)
references
References 51 publications
0
53
1
Order By: Relevance
“…Sample (50 mg) was treated with activated SGF gastric fluid followed by adjusting pH 2.5 using 1 M NaOH and incubated at 37ºC for 2 hr at 50 rpm in incubator shaker. Aliquots were further analyzed for phenolic estimation and release determination using UPLC (Mao & McClements, 2012; Zhang, Zhang, & McClements, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Sample (50 mg) was treated with activated SGF gastric fluid followed by adjusting pH 2.5 using 1 M NaOH and incubated at 37ºC for 2 hr at 50 rpm in incubator shaker. Aliquots were further analyzed for phenolic estimation and release determination using UPLC (Mao & McClements, 2012; Zhang, Zhang, & McClements, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Being the bioaccessibility of carotenoids one of their main limitations to exert their bioactivities, this feature should be carefully addressed when selecting a wall material for encapsulation. For instance, alginate has been proposed as a desirable encapsulation matrix for its ability to protect carotenoids from the acidic conditions during gastric digestion, and indeed, Zhang et al (2016) have recently shown that it effectively protected β-carotene from degradation during digestion. However, the encapsulation within alginate beads caused a reduction in β-carotene bioaccessibility due to insufficient release.…”
Section: Encapsulation Of Carotenoidsmentioning
confidence: 99%
“…Among carotenoids, the most important is β ‐carotene (BC) due to its relative abundance and pro‐vitamin A activity . β ‐Carotene is also known for its high antioxidant activity and for reducing certain cardiovascular and eye diseases . Although diets rich in BC are recommended, its inclusion in processed foods is limited due to its low water solubility and chemical instability, which reduce its bio‐accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…18 -Carotene is also known for its high antioxidant activity and for reducing certain cardiovascular and eye diseases. 19,20 Although diets rich in BC are recommended, its inclusion in processed foods is limited due to its low water solubility and chemical instability, which reduce its bio-accessibility. -Carotene also undergoes several transformations along the gastrointestinal tract, which lead to a reduction in its health benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation